Cosmic ray heating in cool core clusters: II. Self-regulation cycle and non-thermal emission - Jacob, Svenja; Pfrommer, Christoph (Monthly notices of the Royal Astronomical Society, 2017)
Self-regulated feedback by active galactic nuclei (AGNs) appears to be critical in balancing radiative cooling of the low-entropy gas at the centres of galaxy clusters and in regulating star formation in central galaxies. In a companion paper, we found steady-state solutions of the hydrodynamic equations that are coupled to the cosmic ray (CR) energy equation for a large cluster sample. In those solutions, radiative cooling in the central region is balanced by streaming CRs through the generation and dissipation of resonantly generated Alfvén waves and by thermal conduction at large radii. Here, we demonstrate that the predicted non-thermal emission resulting from hadronic CR interactions in the intracluster medium exceeds observational radio (and gamma-ray) data in a subsample of clusters that host radio mini haloes (RMHs). In contrast, the predicted non-thermal emission is well below observational data in cooling galaxy clusters without RMHs. These are characterized by exceptionally large AGN radio fluxes, indicating high CR yields and associated CR heating rates. We suggest a self-regulation cycle of AGN feedback in which non-RMH clusters are heated by streaming CRs homogeneously throughout the central cooling region. We predict radio micro haloes surrounding the AGNs of these CR-heated clusters in which the primary emission may predominate the hadronically generated emission. Once the CR population has streamed sufficiently far and lost enough energy, the cooling rate increases, which explains the increased star formation rates in clusters hosting RMHs. Those could be powered hadronically by CRs that have previously heated the cluster core.